An efficient high-power femtosecond laser based on periodic-layered-Kerr media nonlinear compression and a Yb:YAG regenerative amplifier. (18th February 2022) - Guo, Jie; Gao, Zichen; Sun, Di; Du, Xiao; Gao, Yongxi; Liang, Xiaoyan
Abstract: We demonstrate an efficient ultrafast source with 195 fs pulse duration, 54 W average power at 200 kHz repetition rate and near diffraction-limited beam quality. The compact setup incorporates a thin-disk Yb:YAG regenerative amplifier (RA) and a subsequent nonlinear pulse compression stage with periodic-layered Kerr media (PLKM), which is one of the multiple-thin-solid-plate schemes based on nonlinear resonator theory. In virtue of the formation of quasi-stationary spatial soliton in PLKM, the near diffraction-limited beam quality of the RA remained almost undisturbed after post-compression. The nonlinear pulse compression module is simple and efficient with a transmission of 96%. To the best our knowledge, for pulse energy over 200 μJ, this is the highest output power reported for the multiple-thin-solid-plate scheme. This source manifests an economical combination to mitigate the bandwidth limitations of Yb-based high-power chirped pulse amplifiers.